Esterase profile in the postembryonic development of Rhipicephalus microplus - Baffi, Milla Alves; Pereira, Cícero Donizete; Souza, Guilherme Rocha Lino de; Ceron, Carlos Roberto; Bonetti, Ana Maria (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to analyze the pattern of esterase activity in the development stages of Rhipicephalus microplus by nondenaturing polyacrylamide gel electrophoresis using specific staining for esterase. The electrophoretical results revealed the presence of nine regions displaying esterase activity, stained with both alpha-naphthyl acetate and beta-naphthyl acetate, and classified as alpha-beta-esterase. Stage-specific esterases were found, with the first nymphal and larval stages showing the greatest esterase activity throughout the development. An esterase called EST-4 was detected only in males and was considered sex-specific. There are differences in the esterase profile among the different postembryonic development stages of R. microplus.